An Age-Structured Model for Transmission Dynamics of Malaria with Infected Immigrants and Asymptomatic Carriers - Kalula, Asha S; Mureithi , Eunice; Marijani, Theresia; Mbalawata, Isambi (Tanzania Journal of Science, 2021)
Abstract An age-structured (children and adults) model for the transmission dynamics of malaria with asymptomatic carriers and infected immigrants has been analyzed. We first analyze a model without infected immigrants. It shows that the disease-free equilibrium exists and is stable when and unstable for . Also, we compute the sensitivity indices of the basic reproduction number. The basic reproduction number is most sensitive to the mosquito biting rate. Besides, the sensitivity of the basic reproduction number shows that the children's class parameters are more sensitive than those of adults. In the presence of infected immigrants, the model does not admit a disease-free equilibrium. The sensitivity of endemic equilibrium shows that the asymptomatic carrier parameters are more critical than that of infected immigrants. Also, the inflow of infectious immigrants is sensitive than that of infected immigrants. The results obtained indicate that strategies that target asymptomatic carriers and infected immigrants can help control malaria. Keywords: Age-structure, malaria, immigrants, asymptomatic carrier, nonlinear ODE model.